2015
DOI: 10.1634/theoncologist.2014-0412
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phenotype of Breast Cancer According to Time Since Last Pregnancy in a Large Cohort of Young Women

Abstract: Background. The increase in breast cancer risk during pregnancy and postpartum is well known; however, the molecular phenotype of breast cancers occurring shortly after pregnancy has not been well studied. Given this, we investigated whether nulliparity and the time interval since pregnancy among parous women affects the breast cancer phenotype in young women. Materials and Methods. We examined molecular phenotype in relation to time since pregnancy in a prospective cohort of 707 young women (aged #40 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
7
19
1
Order By: Relevance
“…While the observed associations were strongest close to delivery, there were also findings of interest for tumours diagnosed between 2 and 10 years post-delivery. In line with results from earlier studies [102,[107][108][109][112][113][114], tumours diagnosed during this time window were similar to tumours in nulliparous women with respect to ER status. However, we also found a slightly higher proportion of PR negative tumours, which only has been reported in one previous study [114].…”
Section: Er Pr Her2 Grade and Subtypesupporting
confidence: 90%
See 1 more Smart Citation
“…While the observed associations were strongest close to delivery, there were also findings of interest for tumours diagnosed between 2 and 10 years post-delivery. In line with results from earlier studies [102,[107][108][109][112][113][114], tumours diagnosed during this time window were similar to tumours in nulliparous women with respect to ER status. However, we also found a slightly higher proportion of PR negative tumours, which only has been reported in one previous study [114].…”
Section: Er Pr Her2 Grade and Subtypesupporting
confidence: 90%
“…However, several investigators have reported increased nodal involvement also in women diagnosed with BC up to 10 years post-delivery [70,102,108,112,113], and two studies reported more advanced T stage [70,112]. Most studies have found no evidence of differences in ER or PR status in tumours diagnosed 2-10 years post-delivery compared to tumours in nulliparous women [102,[107][108][109][112][113][114]. Similarly, some studies have reported no difference in grade between tumours detected 2-10 years post-delivery and tumours among nulliparous women [94,113,114], while a few studies reported more high grade tumours in women diagnosed 2-10 years post-delivery [70,102,112].…”
Section: Tumour Characteristics In Bc Around Pregnancymentioning
confidence: 99%
“…Although we found higher rates of PR negative tumors in women diagnosed up to 5 years postdelivery, several studies have found no evidence of increased rates of ER or PR negative tumors or high-grade tumors diagnosed 2-10 years postdelivery. 9,13,18,20,26,27,30 In line with several, 24,25,27,28,32 but not all, 14,22,26 studies we found evidence of an increased mortality rate in women diagnosed 2-5 years postdelivery before adjustment for tumor characteristics. After adjustment for tumor characteristics, the hazard ratios were attenuated and nonsignificant corroborating some of these studies.…”
Section: Tumors Detected 2-10 Years Postdeliverysupporting
confidence: 90%
“…In 2013, Callihan and colleagues showed 2.8-fold and 2.7-fold increases in the risks of metastasis and mortality, respectively, in breast cancer patients diagnosed within the first 5 years post-pregnancy compared to nulliparous cases [18]. In another cohort of parous women diagnosed with breast cancer within the first 5 years postpartum (%40 years of age), the identified tumor subtypes had more aggressive molecular phenotypes such as luminal B-like and triple-negative breast cancer (TNBC) (Box 1) [19]. In accordance with other reports [20][21][22], these findings indicate that postpartum breast cancer patients have a worse clinical prognosis when diagnosed within the first 5 years after giving birth.…”
Section: Pregnancy and Breast Cancermentioning
confidence: 99%